Comparative Real Time EPR Investigation of Natural and Synthetic Antioxidants: As Potential Anticancer Agents and Radio-protectors - Karamalakova, Yanka; Nikolova, Galina; Sharma, Rakesh Kumar; Kumar, Raj; Arora, Rajesh; Zheleva, Antoaneta; Gadjeva, Veselina (Defence Life Science Journal, 2017)
The purpose of this study was to evaluate and compare the free-radical scavenging activity against DPPH stable radical and protective properties of the natural products SQGD and P. corylifolia and synthetic nitroxyl- free radical containing nitrosoureas SLENU and SLCNUgly against in vivo oxidative toxicity of antitumor drug CCNU. It was found statistically significant increase in the DPPH radical-scavenging capacity of both extracts with increase of radiation. The natural antioxidants were localised mainly in the organs and blood after EPR biodistribution study. All combinations of natural extracts/ synthetics agents exhibited considerably lower levels of Asc. radicals as compared to controls. It should be mentioned that the natural antioxidants possess higher oxidative protection in comparison with the synthetic antioxidants. Considerable decrease in ROS production in livers of mice was found after treatment with SQGD, P. corylifolia and SLENU, alone, compared to controls.In conclusion, because of well-expressed antioxidant activities of natural and synthetic antioxidants they might be used in the combination anticancer chemotherapy for reducing toxicity caused by anticancer drugs and/or low levels radiation therapy.